Peningkatan Kompetensi Guru Fisika SMA Provinsi Banten Melalui Pelatihan Pemanfaatan Artificial intelligence (AI) Dalam Pembelajaran - Widiasih; Zakirman; Firmansyah, Juli; Rika, Rika; Nadiyyah, Khoirotun; Handayani, Raden Sumratul (KALANDRA Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aimed to enhance the competence of physics teachers in Banten Province in utilizing Artificial Intelligence (AI) to support innovative and effective teaching practices. The training involved 15 participants and covered topics such as lesson planning using ChatGPT and Canva, creating instructional media with InVideo AI, translating teaching materials with DocTranslator and Deepl, and processing learning outcomes using AI tools. The program was implemented over three days through interactive workshops, practical sessions, and evaluations. Based on the survey results, 90% of participants rated the material quality as excellent, and 92% rated the facilitators’ skills as very good. Additionally, 95% of participants found the training highly beneficial for enhancing their teaching practices. The findings indicate that the training successfully met its objectives and inspired participants to adopt AI in their educational practices. Recommendations include conducting follow-up training and providing implementation support for integrating AI in schools.